Sosialisasi dan Edukasi Pemanfaatan Biopolimer dengan Tema Matematika pada Pemuda Muhammadiyah Kampar - Agus Dahlia; Sapitri Sapitri; Novia Rita; Muhammad Khairul Afdhol; Al Wafi Nazwan Tambusai; Ihsan Alghifari (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Agricultural waste is one of the environmental problems that is still often found in the community, including in Kampar Regency, Riau. The abundant potential of agricultural waste has not been fully utilized into useful products. This community service activity aims to increase the understanding and awareness of Kampar Muhammadiyah Youth regarding the use of agricultural waste as a basic material for environmentally friendly biopolymers and to introduce the application of simple mathematical concepts in the processing and analysis of biopolymers. The activity was carried out for 20 participants through five stages, namely socialization, training, application of simple technology, mentoring and evaluation, and preparation of a sustainability plan. The evaluation was carried out using a participant observation sheet, directed questions and answers, and a simple questionnaire before and after the activity in three main aspects. The evaluation results showed an increase in participants' understanding of the aspect of agricultural waste from 40% to 85%, the concept of biopolymers from 30% to 80%, and the application of simple mathematics from 35% to 75%. In addition, the activity produced outputs in the form of simple biopolymer products, material composition guidelines, and follow-up plans with partners for the development of agricultural waste-based products. Participants showed active involvement in discussions and practices, especially when determining the composition of materials and observing changes in product results. Thus, the integration of biopolymer education and simple mathematics has the potential to be an applicable, contextual approach to community empowerment that supports environmental awareness based on local potential.